Change management for academic leaders and its relationship to the job engagement of faculty members in the Colleges of Physical Education and Sports Sciences in Baghdad - Khudair, L.Dr. Maitham Habib (Sulaimani Journal for Humanities, 2026)
This research aimed to identify the relationship between change management by academic leaders and the job engagement of faculty members in the Colleges of Physical Education and Sports Sciences in Baghdad. The researcher adopted a descriptive approach using correlational methods. The research population consisted of faculty members in the Colleges of Physical Education and Sports Sciences at Al-Mustansiriya and Baghdad Universities, totaling 433 faculty members. The research sample was selected using a random sampling method (lottery) at a rate of 80%, resulting in a sample size of 353 faculty members. The researcher concluded that college deans provide significant incentives and motivation to faculty members to foster healthy competition. The researcher recommended that academic leaders prioritize the ongoing psychological development of faculty members through training courses. Furthermore, the researcher concluded that college deans provide continuous encouragement to faculty members to unleash their potential and knowledge, thereby improving their scientific productivity.
Keywords: Change management; job engagement